GROWTH PERFORMANCE OF SWAMP BUFFALO CALVES HOUSED UNDER DIFFERENT ROOF COVERINGS* - LASKAR1, S. K.; AMONGE, T. K.; GOGOI, A. K.; Das, G.; HAZARIKA, H.; HAZARIKA, D. (Indian Journal of Animal Production and Management, 2017)
An experiment was undertaken at ‘Network Project on Swamp Buffalo’, College ofVeterinary Science, Assam Agricultural University, Khanapara, Guwahati-22 to study thegrowth performance of swamp buffalo calves of Assam housed under different roofcoverings. Eighteen growing swamp buffalo calves (of either sex) of about 5-6 months ofage were selected and housed under three different roof coverings with six calves undereach roof covering. The experimental groups, viz. T1, T2 and T3 were allocated toasbestos roof covering, asbestos roof covering with bamboo ceiling, and thatch roofcovering respectively. The calves were provided with ad libitum chaffed green foragesalong with concentrate mixture at the rate of 0.5 per cent of their body weight. Nosignificant difference was observed in growth performance, daily body weight gain, linearbody measurements, average daily feed and water intake among the calves of the threegroups